Magnetic Nanoparticles: Multimodal Magnetic Nanoclusters for Gene Delivery, Directed Migration, and Tracking of Stem Cells (Adv. Funct. Mater. 25/2017). (3rd July 2017) - Park, Ji Sun; Park, Wooram; Park, Sin‐jung; Larson, Andrew C.; Kim, Dong‐Hyun; Park, Keun‐Hong
Abstract : In article number1700396, Keun‐Hong Park and co‐workers report all‐in‐one magnetic nanoclusters for gene delivery, directed migration, and tracking of stem cells. The magnetic nanoclusters show high transfection efficacy, allow for directing migration of stem cells under magnetic fields, and provide a multimodal imaging modality to enable tracking of the stem cells.